The effect of silver nanoparticles on the antimicrobial activity of cloned nisin against extensively drug-resistant Acinetobacter baumannii" - Meqdad Saleh Ahmed; Zirak.F.A. Abdulrahman; Zanan Mohammed Ameen Taha (Elsevier, 2024)
Background: Antibiotic resistance is a global threat to human health that leads to disasters. Acinetobacter baumannii cannot be controlled by the existing antibiotics, and it became challenging. Therefore, novel antibacterial agents are required to combat such threats. The aim of this project is to find a novel antimicrobial agent to treat this multi-drug resistant bacterium. Methods: The NisA gene was isolated from Lactococcus lactis spp. lactis and cloned into the pET-3a plasmid using Gibson cloning assembly. Purified Nisin from cloning was conjugated with silver nanoparticles. Finally, an assessment of antibacterial activity for each of the purified Nisin, Silver nanoparticles, and Nisin-Silver nanoparticles conjugate against the extensively drug-resistant A. baumannii was performed. Results: Nisin was successfully purified from cloned bacteria, and the concentration was 416 µg/ml. The conjugation of nisin and silver nanoparticles was analyzed by electron microscopy. The minimum inhibitory concentration of Nisin and silver nanoparticles against A. baumannii were 104 µg/ml and 125 µg/ml, respectively. While Nisin-silver nanoparticle conjugates showed potent antimicrobial activity with MIC 125-52 µg/ml in which silver nanoparticles increased the antimicrobial activity of nisin beyond its optimum concentration (104 µg/ml). ‎ Conclusion: The development of new antibacterial agents is necessary to control extensively drug-resistant bacteria. Nisin-silver conjugates showed more potent antimicrobial activity than when applied separately and gave hope to combat the multi-drug resistant A. baumannii.